2022
DOI: 10.1021/acsbiomaterials.2c00794
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Fluorescence/Ultrasound Imaging with Biocompatible Metal-Doped Graphene Quantum Dots

Abstract: Sonography offers many advantages over standard methods of diagnostic imaging due to its non-invasiveness, substantial tissue penetration depth, and low cost. The benefits of ultrasound imaging call for the development of ultrasound-trackable drug delivery vehicles that can address a variety of therapeutic targets. One disadvantage of the technique is the lack of highprecision imaging, which can be circumvented by complementing ultrasound contrast agents with visible and, especially, near-infrared (NIR) fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…Due to its small amount, the metal dopant is not expected to affect the biocompatibility of the GQDs. 65 Besides Nd, EDX analysis indicates carbon, oxygen, and nitrogen, suggesting the presence of various functional groups in the GQD structure. FTIR spectra of freeze-dried GQD samples (Figure S3) indicate that hydroxyl, carboxyl, and amino groups are most likely present on the surface of the GQDs, enabling high water solubility as well as complexation with nucleic acids 50 and covalent functionalization for biological applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its small amount, the metal dopant is not expected to affect the biocompatibility of the GQDs. 65 Besides Nd, EDX analysis indicates carbon, oxygen, and nitrogen, suggesting the presence of various functional groups in the GQD structure. FTIR spectra of freeze-dried GQD samples (Figure S3) indicate that hydroxyl, carboxyl, and amino groups are most likely present on the surface of the GQDs, enabling high water solubility as well as complexation with nucleic acids 50 and covalent functionalization for biological applications.…”
Section: Resultsmentioning
confidence: 99%
“…EDX spectra demonstrate ∼1 atom % of Nd in Nd-NGQDs, confirming their successful doping. Due to its small amount, the metal dopant is not expected to affect the biocompatibility of the GQDs . Besides Nd, EDX analysis indicates carbon, oxygen, and nitrogen, suggesting the presence of various functional groups in the GQD structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we demonstrated that GQDs doped with various metals generate up to a 10-fold ultrasound signal enhancement compared to that of nonmetal-doped GQDs and water control in vascular phantom, agarose gel, and animal tissue. 23 In order to test the ability of Al-GQDs to enhance the ultrasound signal, they are also introduced into these simulated bioenvironments and imaged with the GE Logiq E portable ultrasound system. While nearly no ultrasound signal is detected from water control within 3% agarose gel (Figure 6a), substantial ultrasound signal enhancement is immediately observed after the injection of Al-GQDs (Figure 6b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In such instances, neodymium and thulium-doped GQDs offer in vitro, ex vivo, and in vivo NIR imaging, enabling noninvasive image tracking in live mice, while retaining high biocompatibility. Incorporating metal dopants into the GQD platform also produces biocompatible nanostructures with additional ultrasound contrast capablities. Such multimodality is enabled by a simple and scalable bottom-up GQD synthesis from the plethora of carbonaceous precursor materials. Moreover, GQD structures can be synthetically tailored to facilitate specific therapeutic functions, such as targeting disease sites, delivering drug and gene medicine, and assisting with photothermal ablation .…”
Section: Introductionmentioning
confidence: 99%